2023
DOI: 10.1007/s11739-023-03231-w
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19 vaccinated and unvaccinated patients admitted to Careggi University Hospital, Florence, Italy

Abstract: More than 11.5 billion COVID-19 vaccine doses have been administered around the world. Although vaccine effectiveness for severe infections is reported to be 89.0%, breakthrough infections are common and may lead to severe outcome in fragile population. We conducted a real-world observational study on 420 COVID-19 admitted patients from July 2021 to January 2022 in a tertiary level Italian hospital. We collected patient’s vaccination and SARS-CoV-2 serological status, SARS-CoV-2 treatments, oxygen supports, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…It has been shown that in patients with diabetes mellitus, there is an increased expression of ACE-2, the main receptor of SARS-CoV-2, in the lung and other organs ( 90 ), which situates diabetic patients at increased risk. Paggi et al ( 82 ) demonstrated, with 420 COVID-19 positive patients, that the vaccinated group had a higher Charlson comorbidity index compared to the unvaccinated group ( 82 ), where the most frequent diseases were cardiovascular diseases, pulmonary diseases, renal diseases, diabetes mellitus, dementia, cancer, and hematological diseases. No difference in terms of in-hospital mortality, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in patients with diabetes mellitus, there is an increased expression of ACE-2, the main receptor of SARS-CoV-2, in the lung and other organs ( 90 ), which situates diabetic patients at increased risk. Paggi et al ( 82 ) demonstrated, with 420 COVID-19 positive patients, that the vaccinated group had a higher Charlson comorbidity index compared to the unvaccinated group ( 82 ), where the most frequent diseases were cardiovascular diseases, pulmonary diseases, renal diseases, diabetes mellitus, dementia, cancer, and hematological diseases. No difference in terms of in-hospital mortality, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19-associated mortality is notably increased by aging, disabilities, and underlying medical conditions [14,[19][20][21]. However, data regarding the relationship between COVID-19 outcome and active or latent TB are few and discordant in the available literature.…”
Section: Discussionmentioning
confidence: 99%